Spatial Distribution of Natural Tourism Potentials and Rural Development of Host Communities in Some Selected Areas of Ekiti State, Nigeria - Bankole, _______; Toyin, Dada; Jegede, _____ (International Research Journal of Management, IT & Social Sciences, 2015)
This study examined the spatial distribution of natural tourism potentials and rural development of host communities in some selected Areas of Ekiti State, Nigeria. Natural tourism potentials gives the tourism industry great respect among other industries in Ekiti State, as well as a major concern to business men and women, tourists, government officials, and the general public. Data for this study were collected from personal survey and the random administration of one hundred and fifty (150) questionnaires on respondents in the study area. Results from this study showed that tourists vary frequently, visit the touristsâ potential sites, due to a large number of touristsâ attraction sites in the area. This study recommended that, there is need for improvement of touristsâ potential sites in the study area. This study will be of great help to tourists, environmentalistsâ, researchers, planners and policy makers in the tourism industry, as well as boost the economy of Ekiti State and in-turn impact positively on the development of the State.